Relationship of baseline HDL subclasses, small dense LDL and LDL triglyceride to cardiovascular events in the AIM-HIGH clinical trial. (August 2016) - Albers, John J.; Slee, April; Fleg, Jerome L.; O'Brien, Kevin D.; Marcovina, Santica M.
Abstract: Background and aims: Previous results of the AIM-HIGH trial showed that baseline levels of the conventional lipid parameters were not predictive of future cardiovascular (CV) outcomes. The aims of this secondary analysis were to examine the levels of cholesterol in high density lipoprotein (HDL) subclasses (HDL2-C and HDL3-C), small dense low density lipoprotein (sdLDL-C), and LDL triglyceride (LDL-TG) at baseline, as well as the relationship between these levels and CV outcomes. Methods: Individuals with CV disease and low baseline HDL-C levels were randomized to simvastatin plus placebo or simvastatin plus extended release niacin (ERN), 1500 to 2000 mg/day, with ezetimibe added as needed in both groups to maintain an on-treatment LDL-C in the range of 40–80 mg/dL. The primary composite endpoint was death from coronary disease, nonfatal myocardial infarction, ischemic stroke, hospitalization for acute coronary syndrome, or symptom-driven coronary or cerebrovascular revascularization. HDL-C, HDL3-C, sdLDL-C and LDL-TG were measured at baseline by detergent-based homogeneous assays. HDL2-C was computed by the difference between HDL-C and HDL3-C. Analyses were performed on 3094 study participants who were already on statin therapy prior to enrollment in the trial. Independent contributions of lipoprotein fractions to CV events were determined by Cox proportional hazards modeling. Results: Baseline HDL3-C was protective against CV events (HR: 0.84, p  = 0.043) while HDL-C, HDL2-C, sdLDL-C and LDL-TG were not event-related (HR: 0.96, p  = 0.369; HR: 1.07, p  = 0.373; HR: 1.05, p  = 0.492; HR: 1.03, p  = 0.554, respectively). Conclusions: The results of this secondary analysis of the AIM-HIGH Study indicate that levels of HDL3-C, but not other lipoprotein fractions, are predictive of CV events, suggesting that the HDL3 subclass may be primarily responsible for the inverse association of HDL-C and CV disease.